O desenvolvimento da memória cultural na compreensão da psicologia histórico-cultural : contribuições para os processos de aprendizagem e desenvolvimento - Beppu, Eloisa Atsue Tanaka (2011)
On this research, the process of memory development was approached mainly to understand the process of changing from a primitive or elementary condition to a superior or cultural one considering the importance of the memory for psychic system functioning, as well as, the human being voluntary behavior under the perspective of Historic - Cultural Psychology and based on historic and dialectic materialism. In order to achieve a better outline some specific objectives were also defined: 1) Connecting the cultural memory development to the conceptual thinking; 2) Presenting and analyzing one of the main tasks from school, which is the development of scientific concepts; 3) Reaching the overcoming of dichotomies existing on psychology through the proposal of an educational psychology based on Cultural - Historical Psychology. To accomplish such results, studies were done over the main Russians author L. S. Vigotski, A. R. Luria and A. N. Leontiev, as well as, over other theories on the same perspective about memory development process and also about the proposals for schooling process. Trying to understand how memory development has been studied these days, texts about this issue have been gathered in two large indexes - Capes and Scielo. The results of such collecting, "State of Art", about the research object revealed that nearly all papers are about people's memory, experiences, places, etc, or as a group of neurochemical processes. It goes to show the importance of the study of conceptual memory genesis from Cultural - Historical Psychology, trying to achieve the overcoming of reductionists approaches given to this topic. This way, the result of this research was organized as it follows: Section I reveals the results of research about the issue with regard to the universe of scientific publications; In Section II, it shows the description of memory development process from birth along with psychic functioning led by instincts up to its functioning in a qualitatively superior level of logical or cultural memory. At last but not least, section III shows the relationship between cultural memory and conceptual thinking, the influences of schooling process on the formation of this superior memory, as well as, a proposal of overcoming for performance on educational psychology based on theoric perspective researched. This material showed that Cultural - Historical Psychology has in its purpose the viability for overcoming reductionist views about memory that sometimes focuses on spiritual aspects and sometimes on neurochemical ones which enables the development of potentialities.